Efforts of the Samapta Patrol Unit to Prevent the Crime of Motor Vehicles Theft in Klaten Police - Dicky Sirait (Advances in Police Science Research Journal, 2022)
The author raised the final task with the problem of "Efforts of The Samapta Patrol Unit to Prevent Motor Vehicle Theft in Klaten Police". The writing of this final task aims to identify the implementation of patrols of the Samapta Unit of Klaten Police and identify efforts to increase patrols of the Samapta Unit of Klaten Police. This research uses a qualitative approach with this type of field research research by conducting resource interviewes, observations, and document studies. In addition, the data used is also obtained from various references such as articles, journal books and online media news that are relevant to the variable problems discussed. This research uses management theory and SWOT analysis theory and several concepts relevant to the problem, namely the concept of patrol based on Perkabaharkam No. 1 of 2017 concerning Patrols, the concept of effort, the concept of motor vehicle theft. The Klaten Police Samapta Unit became the backbone in preventive police actions in preventing criminal acts in the klaten police jurisdiction, especially Curanmor. In the implementation of patrols by the Samapta patrol unit, Klaten Police still found some shortcomings in terms of planning, organizing, implementation and supervision and not in accordance with the Patrol SOP that has been regulated in Perkabaharkam Number 1 of 2017 concerning Patrols. In addition, the existence of factors that affect both internally and externally makes the implementation of patrols of the Klaten Police Samapta Unit cannot be carried out optimally. On the other hand, to improve the implementation of patrols, creative breakthroughs are needed in efforts to improve patrol implementation.